Contributions From Teaching to University Extension. Case: Practice of Formulation, Evaluation and Management of Projects, Developed at the School of Planning and Social Promotion of the National University - Chavarría Briceño, Randy (2022)
This article aims to show an experience concerning the link between teaching and university extension from the course “Practice of Formulation, Management, and Evaluation of Projects” proposed in the Economic and Social Planning career program of the National University of Costa Rica. It seeks to show results from interviews with students and teachers. It also aims to identify the advantages of developing teaching processes that allow the university to approach communities through actions generating spaces for participation and dialogue of different types of knowledge, highlighting not only the contribution to groups or organizations in vulnerable sectors but also the achievements and learning for the students in their academic training, which at the same time provides feedback for teaching.